Steering epistemic access in higher education in South Africa institucional dilemmas - Cross, Michael (CLACSO, 2018)
The coup forces that assaulted Brazil want to make tabula rasa of this legacy, hiding the facts to the population and destroying the extraordinary accomplishments of this virtuous historical period. Therefore, this work is an outline to reveal and analyze this legacy. Not only to show what was done in the past, but principally to reveal what can be done in the future, as well. We are convinced that if Brazil overcomes the coup, the destruction of the State and of the world of work by their extremely regressive measures, and promotes a new cycle of development, the basis for such improvement should be based on the legacy of the governments of the PT.